1997
DOI: 10.1103/physrevd.56.3711
|View full text |Cite
|
Sign up to set email alerts
|

Monopoles and instantons on partially compactifiedD-branes

Abstract: Motivated by the recent D-brane constructions of world-volume monopoles and instantons, we study the supersymmetric SU (N ) Yang-Mills theory on S 1 × R 3+1 , spontaneously broken by a Wilson loop. In addition to the usual N −1 fundamental monopoles, the N -th BPS monopole appears from the Kaluza-Klein sector. When all N monopoles are present, net magnetic charge vanishes and the solution can be reinterpreted as a Wilson-loop instanton of unit Pontryagin number. The instanton/multi-monopole moduli space is exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
375
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 211 publications
(383 citation statements)
references
References 28 publications
8
375
0
Order By: Relevance
“…In addition to the monopoles that contributed to (16), there is one more non-trivial gauge field configuration that contributes, which is the Kaluza-Klein monopole. This is present due to the existence of large gauge transformations along the S 1 [35].…”
Section: N = 2 Deformations In D =mentioning
confidence: 99%
“…In addition to the monopoles that contributed to (16), there is one more non-trivial gauge field configuration that contributes, which is the Kaluza-Klein monopole. This is present due to the existence of large gauge transformations along the S 1 [35].…”
Section: N = 2 Deformations In D =mentioning
confidence: 99%
“…Therefore these objects carry both electric and magnetic charges. In the 3+1-dimensional SU(2) gauge theory there are in fact two types of self-dual dyons [48]: M and L with (electric, magnetic) charges (+, +) and (−, −), and two types of anti-self-dual dyonsM andL with charges (+, −) and (−, +), respectively. Their explicit fields can be found e.g.…”
Section: Dyons and Calorons With Non-trivial Holonomymentioning
confidence: 99%
“…In recent years there has been some interest in the connection between magnetic monopoles and instantons in theories with partially compactified space [1,2,3]. Especially by employing the Tduality on D-branes, we have shown that a single instanton in the theory with SU n gauge group on space R 3 × S 1 can be interpreted as a composite of n distinct fundamental monopoles [1].…”
mentioning
confidence: 99%